TANGGUNG JAWAB HUKUM NOTARIS TERHADAP PEMBUATAN AKTA PERJANJIAN NOMINEE SAHAM - Chandra Lesmana (Universitas Sriwijaya, 2016)
The making of the deed of Covenant nominee of shares may cause harm to the parties as a result of the Treaty of nominee shares annulled by law so that it will bring a notary into the legal responsibility and can are sanctions in the civil code, namely in the form of reimbursement of the costs, damages and interest. Criminal sanctions, namely when the existence of fraud or trickery that is sourced from a notary itself, and criminal sanctions may be provided with a review of whether the notary meets the entire contents of the outline of the crime. In addition, by implementing a manufacturing certificate stock nominee agreement then the notary has been doing against the law and may be subject to administrative sanctions, namely in the form of an oral reprimand, written reprimand, suspension, dismissal with respect and stop with disrespect. As well as violating the code of ethics the notary public so it can be charged penalties in the form of a reprimand, warning, suspension of the membership of the Assembly, the Assembly from the membership of the dismissal, and dismissal with no respect from the membership of the Assembly.